UPAYA MENINGKATKAN KEMAMPUAN MENGHAFAL QS. AL-MA’UN MELALUI MEDIA YOUTUBE PADA PESERTA DIDIK KELAS V SDN 246 PALEMBANG - Nurudin, Muhammad; Satra, Alihan Putra; Imtihana, Aida (Guruku: Jurnal Pendidikan Profesi Guru, 2023)
The purpose of this study was to determine efforts to improve the memorization ability of Grade 5 students of SDN 246 Palembang through Youtube-based audio-visual media with the achievement of the results of students' average memorization skills and observation of learning outcomes, both activeness, enthusiasm, attention during lessons.The model in this study uses classroom action research which consists of 4 stages, namely; planning, execution of actions, observation and reflection. The results of this study can be explained as follows: 1) The ability to memorize QS. Al-Ma'un experienced an increase after going through several stages of the cycle. This is shown from the results of oral tests that were originally memorized only 28.13% in the pre-cycle. Then it rose to 65.63% in cycle I and the required action cycle in phase II with the results of achieving completeness value indicators 32 students with 100% memorization achievement were declared successful because they had achieved performance indicators. 2) there is an increase and change in the results of student learning observations from pre-cycle by 57.42% to 77.15% in cycle I and finally in the very good category of 87.70% in cycle II. That is, these results show a change in students becoming more active in learning during the learning process.